Sustained invisibility through crowding and continuous flash suppression: a comparative review - Faivre, Nathan; Berthet, Vincent; Kouider, Sid (Frontiers in Psychology, 2014)
The study of nonconscious vision benefits from several alternative methods that allow the suppression of an image from awareness. Here, we present and compare two of them that are particularly well-suited for creating sustained periods of invisibility, namely visual crowding and continuous flash suppression. In visual crowding, a peripheral image surrounded by similar flankers becomes impossible to discriminate. In continuous flash suppression, an image presented to one eye becomes impossible to detect when rapidly changing patterns are presented to the other eye. After discussing the experimental specificities of each method, we give a comparative overview of the main empirical results derived from them, from the mere analysis of low-level features to the extraction of semantic contents. We conclude by proposing practical guidelines and future directions to obtain more quantitative and systematic measures of nonconscious processes under prolonged stimulation.